Analisis Penerapan Activity Based Management Untuk Meningkatkan Efisiensi Biaya Produksi (Studi Kasus: UMKM Pinkponk Snack Malang) - Syafaatul Utmarila Ihza Waluyo; Andi Asdani; Sumiadji Sumiadji (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
This study aims to examine the calculation of production costs and the potential for improving cost efficiency through the implementation of Activity Based Management at UMKM Pinkponk Snack Malang. Currently, Pinkponk Snack still uses a conventional method for calculating production costs, which tends to be less accurate in allocating overhead costs. Therefore, the Activity Based Costing (ABC) approach is used as a basis to identify activities consumed during the production process. Subsequently, the ABM method is applied to evaluate value added and non value added activities in order to enhance cost efficiency. This research employs a descriptive quantitative approach, with data collected through interviews and documentation. The results show that ABM implementation can identify non value added activities such as packaging and storage, which are recommended to be reduced or optimized. By applying ABM, Pinkponk Snack is able to significantly improve production cost efficiency without compromising product quality. Thus, ABM can serve as an effective strategy for cost control and enhancing the competitiveness of MSMEs in a dynamic market environment.